Peran Sistem Informasi Manajemen dalam Meningkatkan Kualitas Pengambilan Keputusan Manajerial: Studi Literatur - Theodorus Kristianto (Journal of Literature Review, 2026)
This study aims to examine the role of Management Information Systems (MIS) in improving the quality of managerial decision-making through a literature review approach. The review covers 20 previous studies that explore the relationship between MIS implementation and decision-making effectiveness across various sectors, including government, education, business, and healthcare. The findings indicate that MIS plays a crucial role in providing accurate, relevant, and timely information, which assists managers in analyzing problems, evaluating alternatives, and making more rational decisions. Furthermore, the integration of MIS with digital technologies such as big data, cloud computing, and artificial intelligence enhances organizations’ capability for data-driven decision-making. However, the effectiveness of MIS implementation still depends on human resources, top management support, and technological infrastructure readiness. Overall, this study emphasizes that MIS is not merely an administrative tool but a strategic instrument that strengthens organizational competitiveness in the digital era